Abracadabra flute & clarinet duets: elementary - MOZART, W.A. (A & C Black, 1995)
Last of the summer winenMinuetnAndantenThe mocking birdnThe yellow rose of TexasnPortsmouthnWater come a me eyenPaysanenRondeaunI have a song to sing-onScarborough fair